An Overview of Noble Metal-Based Nanoparticles in Medicine - Kle,bowski, Bartosz; Depciuch, Joanna; Parlin´ ska-Wojtan, Magdalena; Baran, Jarek (Current Advances in Chemistry and Biochemistry Vol. 5, 2021)
Nanoparticles have unique, size-dependent properties, which means they are widely used in various branches of industry. The ability to control the properties of nanoparticles makes these nanomaterials very interesting for medicine and pharmacology. The application of nanoparticles in medicine is associated with the design of specific nanostructures, which can be used as novel diagnostic and therapeutic modalities. There are a lot of applications of nanoparticles, e.g., as drug delivery systems, radiosensitizers in radiation or proton therapy, in bioimaging, or as bactericides/fungicides. This paper aims to introduce the characteristics of noble metal-based nanoparticles with particular emphasis on their applications in medicine and related sciences. The development of nanotechnology has opened new doors for more effective treatment and diagnosis of various diseases.